Impact of Health System Affiliation on Hospital Resource Use Intensity and Quality of Care. (22nd December 2016) - Henke, Rachel Mosher; Karaca, Zeynal; Moore, Brian; Cutler, Eli; Liu, Hangsheng; Marder, William D.; Wong, Herbert S.
Abstract : Objective: To assess the impact of hospital affiliation, centralization, and managed care plan ownership on inpatient cost and quality. Data Sources: Inpatient discharges from 3, 957 community hospitals in 44 states and American Hospital Association Annual Survey data from 2010 to 2012. Study Design: We conducted a retrospective longitudinal regression analysis using hierarchical modeling of discharges clustered within hospitals. Data Collection: Detailed discharge data including costs, length of stay, and patient characteristics from the Healthcare Cost and Utilization Project State Inpatient Databases were merged with hospital survey data from the American Hospital Association. Principal Findings: Hospitals affiliated with health systems had a higher cost per discharge and better quality of care compared with independent hospitals. Centralized systems in particular had the highest cost per discharge and longest stays. Independent hospitals with managed care plans had a higher cost per discharge and better quality of care compared with other independent hospitals. Conclusions: Increasing prevalence of health systems and hospital managed care ownership may lead to higher quality but are unlikely to reduce hospital discharge costs. Encouraging participation in innovative payment and delivery reform models, such as accountable care organizations, may be more powerful options.